Lysosomal enzyme cytochemistry in acute leukaemia - Mann, J. R. (1971)
A cytochemical study of the lysosomal enzyme β-glucuronidase in 60 cases of acute leukaemia has shown a qualitative difference in the cytoplasmic distribution of the enzyme between blast cells of the lymphoid and myeloid cell series. This difference provides a useful additional method for cytochemical classification of cell type and is superior in this respect to the other lysosomal enzymes studied (aryl sulphatase and acid phosphatase). The β-glucuronidase reaction is recommended in those cases of acute leukaemia in which the periodic acid-Schiff reaction is negative or equivocal.